Gendered fields: Women, men, and ethnography - Karim, Wazir-Jahan Begum; Bell, Diane; Caplan, Pat (Routledge, 2013)
Examines and explores the progress of feminist anthropology, the gendered nature of fieldwork itself, and the articulation of gender with other aspects of the persona of the ethnographer.
Keywords: anthropologie; approches et analyses; discipline; ethnographie; genre; outils; ouvrages de références; point de vue situé; sciences humaines